Effect of Co-administration of Ketoconazole on Attainment of Desired Blood Concentration of Tacrolimus in Renal Transplant Recipients: Ketoconazole impact on tacrolimus in renal transplant - V, Sivakumar; MS, Soorya; M, Rakshna; Pranesh S (Iranian Journal of Pharmaceutical Sciences, 2025)
Achieving and maintaining optimal tacrolimus trough levels for immunosuppression is challenging in kidney transplant patients due to its narrow therapeutic index. Ketoconazole is known for inhibiting the drug efflux activity of P-glycoprotein and CYP3A enzymes, which are involved in tacrolimus pharmacokinetics. Therefore, there is a need to investigate tacrolimus–ketoconazole coadministration. The study aims to assess the effect and safety of tacrolimus-ketoconazole coadministration in renal transplant recipients. Ethical approval was obtained from the Institutional Human Ethics Committee (IHEC/2023/038) to conduct an ambispective observational study on 14 renal transplant recipients. Tacrolimus total daily dose (TDD) and trough levels were measured before and after initiating oral ketoconazole. The concentration/dose (C0/D) ratio was calculated, followed by safety assessments, including blood counts and renal function tests. Statistical analyses employed paired t-tests, and the significance level was <0.05. Coadministration resulted in a significant 102.45% increase in tacrolimus trough levels (p<0.001) and a 2.19% reduction (p=0.33) in TDD. The C0/D ratio showed a mean increase of 127.74%. Blood counts remained within normal ranges, but a significant decrease in sodium (p=0.01) and an increase in potassium (p=0.03) were observed within the normal range. Tacrolimus-ketoconazole co-administration in renal transplant recipients demonstrated a substantial elevation in tacrolimus trough levels, suggesting a potential strategy for achieving therapeutic concentrations without escalating tacrolimus doses. Despite significant changes in sodium and potassium, they remained within acceptable ranges, supporting the safety of this coadministration strategy.